Spontaneous mutations in CYC8 and MIG1 suppress the short chronological lifespan of budding yeast lacking SNF1/AMPK - Maqani, Nazif (Microb Cell, 2018)
Chronologically aging yeast cells are prone to adaptive regrowth, whereby mutants with a survival advantage spontaneously appear and re-enter the cell cycle in stationary phase cultures. Adaptive regrowth is especially noticeable with short-lived strains, including those defective for SNF1, the homolog of mammalian AMP-activated protein kinase (AMPK). SNF1 becomes active in response to multiple environmental stresses that occur in chronologically aging cells, including glucose depletion and oxidative stress. SNF1 is also required for the extension of chronological lifespan (CLS) by caloric restriction (CR) as defined as limiting glucose at the time of culture inoculation. To identify specific downstream SNF1 targets responsible for CLS extension during CR, we screened for adaptive regrowth mutants that restore chronological longevity to a short-lived snf1∆ parental strain. Whole genome sequencing of the adapted mutants revealed missense mutations in TPR motifs 9 and 10 of the transcriptional co-repressor Cyc8 that specifically mediate repression through the transcriptional repressor Mig1. Another mutation occurred in MIG1 itself, thus implicating the activation of Mig1-repressed genes as a key function of SNF1 in maintaining CLS. Consistent with this conclusion, the cyc8 TPR mutations partially restored growth on alternative carbon sources and significantly extended CLS compared to the snf1∆ parent. Furthermore, cyc8 TPR mutations reactivated multiple Mig1-repressed genes, including the transcription factor gene CAT8, which is responsible for activating genes of the glyoxylate and gluconeogenesis pathways. Deleting CAT8 completely blocked CLS extension by the cyc8 TPR mutations on CLS, identifying these pathways as key Snf1-regulated CLS determinants.